Legal Review Doctor’s Professional Liability Insurance To Patients - Febrina Lorence Sitepu (Institute Of computer Science (IOCS), 2020)
The cause of disputes that occur between patients and doctors is often due to an alleged medical malpractice carried out by doctors in carrying out their duties as providers of health services to patients, and resulting in losses for patients. Through professional liability insurance, doctors can transfer all risks of a patient's lawsuit against him to the insurer by paying a certain premium, and the insurer provides compensation to the patient who filed the lawsuit. As for the problem in this thesis is how the professional obligations of doctors in providing services to patients and the possibility of malpractice as the basis for the existence of medical professional liability insurance,The research method used in the preparation of this thesis is the normative juridical method. The normative juridical research method is used in this study to conduct searches on legal norms, as well as to obtain data and information contained in various literatures in libraries, research journals, newspapers, magazines, internet sites and so on. Doctors' professional obligations in providing services to patients are regulated in the Indonesian Medical Code of Ethics (KODEKI) and Law No. 29 of 2004 concerning Medical Practice. Broadly speaking, the doctor's professional obligations to the patient are: protecting the life of human beings, being sincere and using all their knowledge and skills for the benefit of the patient, keeping everything he knows about a patient even after the patient dies, performing emergency assistance as a duty. humanity, as well as increase knowledge and follow the development of medical science or dentistry. Medical malpractice is a doctor's behavior that is not right, which violates morals and laws. This malpractice occurs due to negligence in carrying out the practice of the medical profession. Legal liability insurance arises in connection with legal aspects in society where it is possible to sue other parties as individuals or business entities for careless actions or negligence. Arrangements for legal relations between doctors and insurance companies are specifically regulated in insurance policies. The policy is used as evidence that there has been an insurance agreement between the insurer (insurance company) and the insured (doctor). In addition, the regulation of legal relations between doctors and insurance companies is also regulated in the Commercial Code, the Civil Code, and Law no. 23 of 1992. The forms of risk that can be transferred by the doctor as the insured with the insurance company as the insurer are: bodily injury to the patient caused by the actions of the insured that occur in the area of ??coverage during the validity of the policy, actions taken by authorized health workers who are not doctors or doctors teeth that help the insured, events that result in loss and claims from patients, professional liability insurance only applies to compensation for losses that are determined to be located in the country of address of the insured party. So there are several ways to settle disputes over these claims, namely: through peaceful means, through arbitration institutions, through court processes. bodily injury to the patient caused by the actions of the insured that occurred in the coverage area during the validity of the policy, actions taken by authorized health workers who were not doctors or dentists who assisted the insured, events that resulted in losses and claims from patients, liability insurance the medical profession only applies to compensation for losses that are determined to be located in the country of address of the insured party. So there are several ways to settle disputes over these claims, namely: through peaceful means, through arbitration institutions, through court processes. bodily injury to the patient caused by the actions of the insured that occurred in the coverage area during the validity of the policy, actions taken by authorized health workers who were not doctors or dentists who assisted the insured, events that resulted in losses and claims from patients, liability insurance the medical profession only applies to compensation for losses that are determined to be located in the country of address of the insured party. So there are several ways to settle disputes over these claims, namely: through peaceful means, through arbitration institutions, through court processes. events that result in losses and claims from patients, medical professional liability insurance only applies to compensation for losses that are determined to be located in the country of address of the insured party. So there are several ways to settle disputes over these claims, namely: through peaceful means, through arbitration institutions, through court processes. events that result in losses and claims from patients, medical professional liability insurance only applies to compensation for losses that are determined to be located in the country of address of the insured party. So there are several ways to settle disputes over these claims, namely: through peaceful means, through arbitration institutions, through court processes. Based on these explanations and conclusions, the author suggests that professionals should take professional legal liability insurance, especially for doctors to take medical professional liability insurance. It is recommended that efforts to introduce medical professional liability insurance products be increased to protect patients and doctors in the event of medical malpractice. The amount of premium should be adjusted to the condition of doctors and patients in Indonesia. In accordance with the development and progress of the medical profession, the Government should immediately stipulate a provision regarding the medical professional standard.